Fadiga, corrosão-fadiga e corrosão sob tensão em parafusos prisioneiros fabricados em aço inoxidável AISI 304 e o desenvolvimento de um software educacional para as 3 solicitações nestes materiais - Nery, Macclarck Pessoa (2024)
The thesis addresses three major loading conditions to which industrial equipment is subjected: fatigue, corrosion-fatigue, and stress corrosion cracking (SCC). When frequent assembly and disassembly are expected, bolts emerge as a solution. It is common for them to be subjected to fatigue due to cyclic external loads. When the application involves aggressive environments, such as coastal areas, oil platforms, and nuclear power plants, the AISI 304 austenitic stainless steel becomes one of the most popular choices due to its corrosion resistance, good mechanical properties, machinability, formability, and weldability. For stainless steels, higher mean stress reduces the alternating stress in the fatigue life; however, frequency has distinct effects. In corrosion-fatigue, the performance of these materials in chloride environments is deteriorated, and stress corrosion cracking is more common in seawater or chloride solutions. In particular, the study investigated such conditions on studs made of AISI 304 stainless steel and developed educational software about these for stainless steels in general. The objective was to identify and rank among the three requests which one is the most aggressive to the component. The results indicated a deleterious effect of mean stress on fatigue, the reduction in frequency produced an increase in the stress amplitude at the endurance limit of fatigue by up to 160%. The corrosion-fatigue tests conducted in chloride solution showed worse performance, with a reduction of up to 74.5% in stress level at N = 2x106 cycles. There were no SCC failures at room temperature in 278 hours even when exceeding the yield stress. In parallel, an educational software in JAVA was developed for the three themes with textual and infographic content, an endurance limit of fatigue calculator, and links to specific bibliographies. Finally, an usability analysis was conducted using the System Usability Scale among materials engineering and mechanical engineering students, achieving satisfactory rates.